Indonesian Language Learning Based on Ecological Literacy in Improving Students Language Skills - Sri Hastuti; Raheni Suhita (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates the integration of a contextual learning model based on ecological literacy in Indonesian language learning within vocational high schools. The aim is to enhance students' language skills and foster their active participation in learning Indonesian through contextual and relevant experiences. Methodology: The study employs a qualitative descriptive approach, analyzing classroom learning processes. Data sources include speech, actions, and supporting documents collected during the research. Purposive sampling was used to select teachers and students from class X of Vocational High Schools 1 Sawit Boyolali as participants. Research instruments consisted of observation records, interview lists, and documentation. Method triangulation was applied to ensure validity, incorporating observations, interviews, and analysis of classroom learning processes. Data were analyzed descriptively to present detailed findings and draw conclusions. Main Findings: The findings reveal significant improvements in students’ language skills through ecological literacy-based Indonesian learning. The contextual learning model aligns with students’ vocational expertise, enabling them to engage deeply with language in practical and meaningful contexts. This approach not only enhances reading and comprehension skills but also builds students' confidence in expressing ideas verbally and in writing. Novelty/Originality of this study: This study introduces a novel approach by integrating ecological literacy into Indonesian language education, addressing linguistic and environmental awareness. It provides new insights into how contextual learning tailored to students’ vocational fields can enrich language skills, bridging academic content with real-world applications. This research offers a valuable model for innovative and interdisciplinary education.